2011
DOI: 10.1103/physreva.83.045601
|View full text |Cite
|
Sign up to set email alerts
|

Slowing down of vortex rings in Bose-Einstein condensates

Abstract: We consider vortex rings moving in a Bose-Einstein condensate. By numerically solving the Gross-Pitaevskii equation, we show that if the circular shape of the ring is perturbed by helical Kelvin waves of given amplitude and azimuthal wave number, the translational self-induced velocity of the vortex ring is reduced; at large amplitude, the vortex ring halts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…Its dynamics is well established. Recently attention was focused on dynamics of helical-vortex rings with largeamplitude Kelvin waves propagating around the ring [3][4][5]. This problem being interesting itself may have important implications for superfluid turbulence.…”
mentioning
confidence: 99%
“…Its dynamics is well established. Recently attention was focused on dynamics of helical-vortex rings with largeamplitude Kelvin waves propagating around the ring [3][4][5]. This problem being interesting itself may have important implications for superfluid turbulence.…”
mentioning
confidence: 99%
“…In Bose-Einstein condensates (BECs) of ultracold atomic gases, quantized vortex rings have been created through the decay of solitons and directly observed by imaging the density distribution [4][5][6][7]. The dynamics of quantized vortex rings in superfluids have been theoretically studied by many researchers [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Although this was previously studied in Ref. [135], the results shown had very large error-bars and it is unclear how the velocity actually behaves depending on the mode amplitude. The large error-bars there were understandable since they used a vortex ring of radius d = 25 which is quite large, and thus its velocity is slow and hard to track (this can be seen in our velocity results of Fig.…”
Section: Quadrupole Oscillationsmentioning
confidence: 75%
“…A study of vortex rings perturbed by planar and helical Kelvin modes was performed in Ref. [135]. It was found that the Kelvin modes can slow down the vortex We also record the velocity of the ring versus the mode amplitude.…”
Section: Quadrupole Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation